The ICT social inclusion among Orang Asli community in Gombak area - Ahlan, Abdul Rahman; Arshad, Yusri (2011)
As Malaysia is moving towards k-economy and developed nation by 2020, there is a need for all its citizens to participate in this socio-economic development. Orang Asli often have been cited as introverts and lag behind compared to other races in Malaysia. Literatures indicate a few researches have been studied involving the Orang Asli but a dearth is found focusing on ICT education and Internet usage among the Orang Asli schoolchildren. This study aims to fill in this gap by investigating the computer and Internet usage among the Orang Asli schoolchildren in three schools in Gombak area which is close to International Islamic University Malaysia (IIUM) main campus. The survey findings indicate most of the respondents are familiar with computer and Internet but the level of usage varies. Most parents are lower-income earners and affordability to own personal computers become a main issue. Even though schools provide limited time allocations for the students to use computer laboratories, the students also visit cybercafés, friends and relatives’ houses to use computers and Internet.